2020
DOI: 10.1097/mph.0000000000001801
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Insufficiency is Not Associated With Pediatric and Adolescent Immune Thrombocytopenia: A Study in Conjunction With its Receptor Genetic Polymorphisms

Abstract: Idiopathic thrombocytopenic purpura (ITP) is a heterogeneous immunologic disorder. Vitamin D has immune-modulatory effects. The pleiotropic effects of vitamin D are exerted via vitamin D receptor (VDR) and its genetic alterations could influence its functions. In our study, we measured the serum 25-hydroxyvitamin D levels in 98 Pediatric and Adolescent ITP patients, in addition to 100 apparently healthy controls. Genetic polymorphisms of the VDR gene FokI, BsmI, ApaI, and TaqI were tested using specific restri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…No statistically significant differences between cases and healthy controls were observed; both groups had vitamin D insufficiency. Vitamin D deficiency is widespread in healthy children, with recent data indicating that almost 40% of Egyptian children had vitamin D levels ranging between 10 and 20 ng/ml [19]. Vitamin D insufficiency is prevalent in acute and critically ill children and is related to higher mortality, as Cariolou et al observed in a metaanalysis published in 2019 [22].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…No statistically significant differences between cases and healthy controls were observed; both groups had vitamin D insufficiency. Vitamin D deficiency is widespread in healthy children, with recent data indicating that almost 40% of Egyptian children had vitamin D levels ranging between 10 and 20 ng/ml [19]. Vitamin D insufficiency is prevalent in acute and critically ill children and is related to higher mortality, as Cariolou et al observed in a metaanalysis published in 2019 [22].…”
Section: Discussionmentioning
confidence: 98%
“…Catalog number: Ko781; Thermo Fisher Scientific). Polymorphisms in the investigated genes were tested using the polymerase chain reaction-restriction fragment length polymorphism approach (PCR-RFLP) employing specific restriction endonuclease enzymes for each polymorphic site [BsmI, FokI, TaqI, and ApaI for BsmI (rs1544410), FokI (rs2228570), TaqI (rs731236), and ApaI (rs7975232) polymorphic sites, respectively] [19]. These enzymes were used to digest the amplified polymerase chain reaction products.…”
Section: Genotyping Of the Candidate Genesmentioning
confidence: 99%
“…They reported that vitamin D deficiency does not represent a chronicity factor for ITP. According to Shaheen et al, 16 they concluded that vitamin D insufficiency is not associated with Pediatric and Adolescent ITP.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between ITP and vitamin D levels has been studied in a small number of pediatric cases before. [11][12][13][14][15][16] Here in this study, we present for the first time the evaluation of vitamin D levels in adult ITP patients.…”
Section: Discussionmentioning
confidence: 99%